THE RELATION BETWEEN PHYSICAL FITNESS AND LEARNING ACHIEVEMENT OF STUDENTS - Subiyono, Hadi Setyo (JURNAL HEALTH AND SPORT, 2010)
Preliminary study showed that student who were in SKBM (Standard Completeness Minimum Study) for 2nd grade just only 74,30%. The aim of the research is to know the association between physicalfitness, hemoglobin status, nutrition status, breakfast habits and learning achievement of grade II students in MTS Al Asror Gunungpati Semarang. The design used is cross sectional. Sixty five student were studied. The independent variables in this research are physical fitness, hemoglobin status, nutrition status,and breakfast habits. Univariate and bivariate analysis were performed. Three variables have significant association with learning achievement, those are : hemoglobin status, nutrition status, break fast habits. In this study, physical fitness have no significant with learning achievement. Based on research finding, suggested that mts Al Asror to determine health variable (hemoglobin status, nutritional status, and breakfast habit) in order to increase the learning achievement of student.